Fei-Yan-Qing-Hua decoction attenuates influenza virus infection by enhancing host antiviral response through microbiota-derived acetate - Biao Dou; Biao Dou; Biao Dou; Xiao Wu; Xiao Wu; Yurong He; Yurong He; Guihua Xu; Huan Zhang; Huan Zhang; Qilin Huang; Qilin Huang; et al. (Frontiers Media S.A., 2024)
BackgroundFei-Yan-Qing-Hua decoction (FYQHD) is derived from the well-known Ma Xing Shi Gan decoction, which was documented in Zhang Zhong Jing's "Treatise on Exogenous Febrile Disease" during the Han Dynasty. Although FYQHD has been used in the treatment of pneumonia and has demonstrated clinical efficacy for decades, the underlying mechanism by which FYQHD protects against influenza virus infection through modulation of gut flora remains unclear. Here, we examined the regulatory impacts of FYQHD on an influenza virus-infected mouse model and explored the mechanisms involved.MethodsAn infectious mouse model was created by intranasal instillation of influenza A virus (IAV). The effectiveness of FYQHD was assessed through various measures, including weight loss, lung wet/dry ratio, oxidative stress levels, viral load in lung tissues, and intestinal injuries. Changes in gut microbiota and SCFA production were also examined.ResultsThe results showed that FYQHD significantly reduced viral load, increased the production of type I interferon (IFN-I), and restored the integrity of the intestinal barrier following IAV challenge. Additionally, FYQHD significantly corrected the dysbiosis of gut microbiota induced by influenza virus infection, enhancing the abundance of SCFA-producing bacteria and acetate production. However, the depletion of gut microbiota significantly attenuated the protective effects of FYQHD against influenza virus infection. In vitro, the antiviral effect of acetate was demonstrated through the upregulation of concentrations of IFN-β.ConclusionFYQHD attenuates influenza virus-induced lung and intestinal injuries by boosting the host antiviral response through increasing the abundance of Lachnospiraceae_NK4A136 and Roseburia, along with elevated acetate levels. The study advances our understanding of the therapeutic mechanisms of FYQHD and provides a theoretical basis for the application of FYQHD in the treatment of influenza.